The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4049/jimmunol.1200162
|View full text |Cite
|
Sign up to set email alerts
|

Tim-3 Pathway Controls Regulatory and Effector T Cell Balance during Hepatitis C Virus Infection

Abstract: Hepatitis C virus (HCV) is remarkable at disrupting human immunity to establish chronic infection. Up-regulation of inhibitory signaling pathways (such as Tim-3) and accumulation of regulatory T cells (Tregs) play pivotal roles in suppressing antiviral effector T cell (Teff) responses that are essential for viral clearance. While the Tim-3 pathway has been shown to negatively regulate Teffs, its role in regulating Foxp3+ Tregs is poorly explored. In this pilot study, we investigated whether and how the Tim-3 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
91
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 50 publications
8
91
1
3
Order By: Relevance
“…Then, Tim-3 expression is significantly upregulated on iTreg cells and deliver a negative signal tempering Treg expansion and function: blocking Tim-3/Gal-9 ligation further increased the expansion and TGF-β/IL-10 production by Treg cells in the presence of Gal-9 + HCV + Huh-7 cells. These data are consistent with previous evidence showing that both Tim-3 and PD-1, together with the simultaneous TCR/MHC-peptide interaction, negatively regulate the expansion and suppressive function of Treg cells by controlling STAT-5 phosphorylation, at the site of inflammation in chronic HCV infection [17,18]. Therefore, Tim-3, as well as PD-1 [16,17], seem to act as a double-edged sword with the effect dependent on the phase of T cell activation: both Tim-3 and PD-1 can contribute to Treg-cell conversion from naïve Tconv cells, i.e.…”
supporting
confidence: 92%
“…Then, Tim-3 expression is significantly upregulated on iTreg cells and deliver a negative signal tempering Treg expansion and function: blocking Tim-3/Gal-9 ligation further increased the expansion and TGF-β/IL-10 production by Treg cells in the presence of Gal-9 + HCV + Huh-7 cells. These data are consistent with previous evidence showing that both Tim-3 and PD-1, together with the simultaneous TCR/MHC-peptide interaction, negatively regulate the expansion and suppressive function of Treg cells by controlling STAT-5 phosphorylation, at the site of inflammation in chronic HCV infection [17,18]. Therefore, Tim-3, as well as PD-1 [16,17], seem to act as a double-edged sword with the effect dependent on the phase of T cell activation: both Tim-3 and PD-1 can contribute to Treg-cell conversion from naïve Tconv cells, i.e.…”
supporting
confidence: 92%
“…These results are in agreement with our previous observations that another negative signaling molecule, T cell immunoglobulin and mucin domain protein 3 (Tim-3), is upregulated on NK cells to dampen their functions, with inhibited activation (CD69), proliferation (Ki69), degranulation (CD107a), and killing activity (granzyme B) following HCV infection (data not shown). This in turn interplays with monocytes and T cells (including Th17 and Foxp3 ϩ Tregs) in immune dysregulation that contribute to viral persistence (42)(43)(48)(49). This also supports the notion that HCV may utilize KLRG1-an intrinsic mercenary of cell feedback regulation-for the purpose of virus persistence and thus facilitate chronic infection.…”
Section: Discussionsupporting
confidence: 65%
“…TIM-3 binds to its ligand galectin-9, which is expressed on KCs and other myeloid cells, and negatively regulates T-cell response [9]. HCVinfected hepatocytes also express galectin-9 and induce CD4 + CD25 + FOXP3 + Treg infiltration in the diseased liver [45]. Li et al showed that TIM-3 expression is increased in the T lymphocytes infiltrating in HCC [9].…”
Section: Tim-3mentioning
confidence: 99%